Nanocarriers: A novel strategy for the delivery of CRISPR/Cas systems - Hejabi, Faranak; Abbaszadeh, Mohammad Sadegh; Taji, Shirinsadat; O’Neill, Andrew; Farjadian, Fatemeh; Doroudian, Mohammad (Frontiers in Chemistry, 2022)
In recent decades, clustered regularly interspaced short palindromic repeat/CRISPR associated protein (CRISPR/Cas) has become one of the most promising genome editing tools for therapeutic purposes in biomedical and medical applications. However, the safe and effective delivery of CRISPR/Cas systems represents a substantial challenge that must be tackled to enable the next generation of genetic therapies. In addition, there are some challenges in the in-vivo delivery of the targeted cells/tissues. Nanotechnology-based drug delivery systems can be employed to overcome this issue. This review discusses the current CRISPR/Cas delivery systems, including viral and non-viral carriers. The focus then turns to the different nanomaterials, such as liposomes, polymeric, and gold particles, which have been recently used as a nanocarrier for CRISPR/Cas delivery.